Tinjauan Yuridis Terhadap Perjanjian Pemborongan Bangunan Gedung Badan Pengelolaan Pajak Dan Retribusi Provinsi Sumatera Utara - Tuti Indah Sari; Abdul Lawali Hasibuan; Rafiqi Rafiqi (JUNCTO: Jurnal Ilmiah Hukum, 2020)
Implementation of building contract agreement for building "North Sumatra Provincial Tax and Retribution Management Agency at PT. Betesda Makmur "Agreement on building contract for PT. Betesda Mandiri is more than where the party giving the job contract is apart from the private sector besides the emergence of this agreement is simpler that can be by selecting contractors with negotiations and by selecting contractors with limited tenders. The research method used is Normative Juridical, and data collection techniques used are the library research. Implementation of building contract agreement for building "Management of Regional Tax and Retribution in the province of North Sumatra at PT. Betesda Mandiri "Building contract agreement at PT. Betesda Mandiri arises more from the party providing jobs from the private sector. In addition to the process for the emergence of this agreement, it is simpler, that is by selecting contractors, negotiating with a limited selection tender. During the development process there were no obstacles that occurred during the construction, all in accordance with what was planned during the agreement. If there is a party that carries out a default, sanctions may be imposed in accordance with those stated in the agreement.